Custom made ocular prosthesis at Optometry Clinic Universiti Kebangsaan Malaysia (UKM) - Norhani Mohidin; Chia, Jho Yan; Mohd Norhafizun Mohd Saman; Nazeem Desai (penerbit ukm, 2013)
Patients who lost their eyes as results of accidents or diseases (e.g. retinoblastoma) usually underwent enucleation or evisceration. They were then fi tted with ocular prosthesis to prevent collapse of the globe and also for cosmetic effects. Custom made ocular prosthesis is almost unheard of in this country for most hospitals supply ready-made (stock) prosthesis. The cosmetic results of stock prosthesis are often unsatisfactory. Besides being uncomfortable, stock prosthesis may also induce allergic reaction that may lead to papillary conjunctivitis. The Optometry Clinic at UKM started its custom made prosthetic service in 2010. We described here two cases of patients who complained of discomfort with their old stock prosthesis and re-fi tted with custom made prosthesis. We also highlight the importance of proper hygiene and maintenance so that ocular prosthesis can be used for as long as possible. This article aims to create awareness among eye care practitioners and showcase the cosmetic benefi ts of custom made ocular prosthesis.